The ABC of Housing Strategies: Are Housing Assistance Programs Effective in Enhancing Children's Well Being? - Jose Rosero (Tinbergen Institute, 2012)
This paper examines the effect of a housing assistance program on school enrollment, child labor and poverty reduction among poor families in Ecuador. Administrative data is merged to a household panel to link the history of a voucher application with socioeconomic information. Two empirical approaches are employed. First, I exploit variation in duration of the different stages to obtain a voucher and convert it into a house, using a sample of approved applicants. Second, I use variation across siblings that arises from the fact that siblings are exposed to the program at different ages. Results show that the program improves enrollment into post-compulsory education, decreases the probability that a child participates in the labor market and reduces the likelihood to live in poverty. Potential mediating factors are increased access to sanitation, better quality materials of the house and a reduced probability to live overcrowded.
Keywords: H53; I28; I38; R21; 330; Housing assistance programs; Housing voucher; Children; Fixed Effects; Within family estimators; Developing country; Ecuador